The Impact of Cognitive Behavioral Therapy on Peripheral Interleukin-6 Levels in Depression: A Systematic Review and Meta-Analysis - Ma, Haijing; Xu, Jiatong; Li, Ruonan; McIntyre, Roger S.; Teopiz, Kayla M.; Cao, Bing; Yang, Fahui (Frontiers in Psychiatry, 2022)
There is interest in the role of peripheral interleukin-6 (IL-6) in depression and the effect of treatment (e.g., pharmacologic, psychosocial, neurostimulation). However, the relationship between cognitive behavioural therapy (CBT), IL-6 and depression has yet to be established. We conducted a meta-analysis to explore the association between CBT and change of peripheral IL-6 levels in depressive symptoms or major depressive disorder (MDD). A systematic search of online databases (i.e., PubMed, Web of Science, Google Scholar, PsycINFO and Cochrane Library) was completed from inception to May 2021. In total, 10 eligible papers with 940 participants reporting peripheral IL-6 levels before and after CBT were included in the analysis. The main result indicates that peripheral levels of IL-6 were significantly lower after CBT intervention in individuals with depression, with a moderate effect (SMD=0.38, 95% CI: 0.07, 0.69, p=0.02). The results of subgroup analyses demonstrate that (1) there was a significant decrease in IL-6 for studies that were equal to or less than 8 weeks in duration vs. more than 8 weeks in duration, and (2) IL-6 was significantly reduced in the Diagnostic and Statistical Manual of Mental Disorders (DSM) diagnosis (i.e., DSM-IV, DSM-IV-TR, or DSM-V) of MDD, but not for the subgroup without DSM diagnosis. Publication year was identified as a potential contributor to heterogeneity of the results from our analysis. Taken together, our findings support the notion that CBT influences peripheral IL-6 in individuals with depression and represents a point of commonality with other antidepressant treatment modalities (e.g., antidepressants).